Let A B C D be a rectangle such that A B = 5 and B C = 1 2 . There exist two distinct points X 1 and X 2 on B C such that ∠ A X 1 D = ∠ A X 2 D = 9 0 ∘ . Suppose that d is the distance from X 1 to X 2 . What is d 2 ?
This problem is posed by David A .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
A similar solution to that presented, is to let Y 1 be the reflection of X 1 across A D . Then X 1 X 2 Y 1 is a right triangle with X 1 Y 1 = 1 0 , X 2 Y 1 = A D = 1 2 . Hence, X 1 X 2 2 = 1 2 2 − 1 0 2 .
Most solutions hunted down the exact points, and calculated the lengths of B X 1 or C X 2 .
We know that, angle subtended in a right angle. So let us consider a circle with centre on midpoint of A D say O Since ∠ A X 1 D = ∠ A X 2 D We have to take diameter of this circle to be A D . Draw a perpendicular from O to P . O P = 5 Draw segments O X 1 and O X 2 which are radii with radius = 6 We can prove that Δ X 1 P O ≅ Δ X 2 P O by RHS congruency. Hence, X 1 P = X 2 O By considering rt. Δ O P X 2 with hypotenuse O X 2 = 6 by pythagoras theorem we have P X 2 = 1 1 , d = 2 1 1 ⇒ d 2 = 4 4
let DX1 = AX2 = x, AX1 = DX2 = y, and CX1 = BX2 = z by Phytagoras Theorem : x^2 + y^2 = 144 area of rectangle ABCD = 1/2 * 12 * 5 = 30 1/2 * x * y = 30, then y = 60/x.
x^2 + (60/x)^2 = 144 x^4 - 144x^2 + 3600=0 ( x^2 - (72+12 √(11) ) * ( x^2 - (72-12√(11)) ) = 0. x^2 = 72+12 √(11) or x^2 = 72-12 √(11) the value of x must be positive, then x = √(72-12 √(11)) = √66 - √6, y = 72 +12 √(11) = √66 + √6 and z = √((√66 - √6)^2 - 5^2)) = 6 - √11
the value of d^2 = (12 - 2 * z)^2 = (12 - 2 * (6 - √11) )^2 = (2√11)^2 = 44
We have : A ( 0 , 0 ) , B ( 0 , 5 ) , C ( 1 2 , 5 ) , D ( 1 2 , 0 ) , We are trying to find some point M ( x , 5 ) laying on the line BC and verifying that the lines A M and M D are perpendicular this means that : A M ⋅ M D = 0 .
From the coordinates, we get : A M ( x 5 ) , and : M D ( 1 2 − x − 5 ) , Hence we get : x ( 1 2 − x ) − 2 5 = 0 ⟹ x = 6 ± 1 1 . We conclude that there are two possibilities for M as stated in the problem : X 1 ( 6 + 1 1 , 5 ) , X 2 ( 6 − 1 1 ) , the distance between them is : d = 2 1 1 ,
Finally, we have : d 2 = ( 2 1 1 ) 2 = 4 4 .
Let O be the midpoint of A and D . Let θ 1 and θ 2 be ∠ A O X 1 and ∠ D O X 2 , respectively.Let M be the midpoint of X 1 and X 2 .
Because ∠ A X 1 D = ∠ A X 2 D = 9 0 o we can say that X 1 a n d X 2 lies on a circle whose diameter is A D , specifically it's center is O . Let's call this circle γ .
Since A B C D is a parallelogram, then we can say that the perpendicular distance of M to line segment A D is A B = 5 . Since the radius of the circle γ = 2 A D = 6 , then the distance from O to X 1 and X 2 is also 6 .
Thus if we use the pythagorean relation to the right triangle X 1 M O , we can see that X 1 M = 1 1 . Moreover, using the same line of argument X 2 M = 1 1 . It is clear that M O is perpendicular to A D and B C because c o s θ 1 = c o s θ 2 and A B C D is a rectangle.
Therefore the distance, d , from X 1 to X 2 is 2 1 1 . Thus, d 2 = ( 2 1 1 ) 2 = 4 4
Let x1 and x2 divide BC into 3 segments with each of the length is (6-d/2), d, and (6-d/2). Suppose that Ax1 is x and Ax2 is y X^2=25+(6-d/2)^2 Y^2=25+(6+d/2)^2 And also x^2+y^2=144 By subtitution method, we can get d^2=44
Given the rectangle A B C D with A B = C D = 5 and B C = A D = 1 2 , and the two points X 1 and X 2 such that ∠ A X 1 D and ∠ A X 2 D are both equal to 9 0 ∘ . So we draw line segments from A to X 1 , X 1 to D , A to X 2 , and X 2 to D inside A B C D .
Let us focus now on trapezoid A B X 2 D , which is so because A D ∣ ∣ B X 2 . Within A B X 2 D are two triangles, A B X 2 and A X 2 D , which are both right triangles because they contain the right angles ∠ A B X 2 and ∠ A X 2 D , respectively. Also, X 1 is in the segment B X 2 .
Let x be the length of segment A X 2 , y be that of segment D X 2 , z , that of segment B X 1 , and w = z + d ( d is the length of segment X 1 X 2 ; w = length of segment B X 2 ). Furthermore, the side X 2 is common between the triangles A B X 2 and A X 2 D . From these information and the Pythagorean Theorem, A B 2 + B X 2 2 = A X 2 2 and A X 2 2 + D X 2 2 = A D 2 , or equivalently,
1 . 2 5 + w 2 = x 2
2 . x 2 + y 2 = 1 4 4
By substitution, we have 2 5 + w 2 + y 2 = 1 4 4 , or
3 . w 2 + y 2 = 1 1 9 .
Let us now take in triangle D C X 2 , which is also a right triangle because of right angle ∠ D C X 2 . Furthermore, segment D X 2 is the hypotenuse of D C X 2 . So letting a be the length of side C X 2 ,
4 . a 2 + 2 5 = y 2
Another substitution gives us:
5 . w 2 + a 2 = 9 4
Another thing about a is that it is also equal to 1 2 − w . Solving for w in terms of a ( w = 1 2 − a ), and substituting this into 5 :
6 . ( 1 2 − a ) 2 + a 2 = 9 4
Simplifying, and multiplying both sides of the equation by 2 1 :
7 . a 2 − 1 2 a + 2 5 = 0
Using the Quadratic Formula to find a , a = C X 2 = 6 ± 1 1 .
This is one part. The second one comes when we consider trapezoid D C X 1 A with triangles A X 1 D and D C X 1 , and triangle A B X 1 , and the variables are assigned to corresponding segments on both polygons. Using the similar line of argument as the one we had before, we have B X 1 = 6 ± 1 1 .
Finally, it can be verified that B X 1 + X 1 X 2 + C X 2 = B C . Thus, the lengths of B X 1 and C X 2 must not exceed that of B C , which is 12. Out of the two possible values for B X 1 and C X 2 , the only acceptable value is 6 − 1 1 . Therefore, B X 1 = C X 2 = 6 − 1 1 , leaving X 1 X 2 = 2 1 1 , which is the exact value of d . The required answer is d 2 = ( 2 1 1 ) 2 = 4 4 .
using to-ong triangular theorem
let's assume that D X = x
in the right angle triangle A D X :
A X 2 = 5 2 + x 2
and in the right angle triangle X B C
X B 2 = 5 2 + ( 1 2 − x ) 2
and in the right angle triangle A B X
A X 2 = 1 2 2 − X B 2
A X 2 = 1 2 2 − ( 5 2 + ( 1 2 − x ) 2 )
since A X = A X :D we can say that
1 2 2 − ( 5 2 + ( 1 2 − x ) 2 ) = 5 2 + x 2
we can solve this equation easily and we will get that
x = 6 − 1 1 ... which is D X 1
x = 6 + 1 1 ... which is D X 2
we subtract them to get X 1 X 2 = 2 1 1
we square to get 4 4
A X 1 D and A X 2 D lie in the same circle with circumcenter as the midpoint of AD, so the circumradius comes out to be 2 A D = 6 . Draw perpendiculars X 1 E and X 2 F to A D . X 1 E = X 2 E = A B = 5 . In triangle E X 1 O , E X 1 = 5 , X 1 O = 6 . By applying pythagorean theorem on right triangle E X 1 O , we obtain E O = 1 1 . By symmetry we get E O = O F = 1 1
⇒ E F = 2 1 1
Since E X 1 X 2 F is a rectangle.
⇒ X 1 X 2 = E F = 2 1 1
⇒ X 1 X 2 2 = 4 4
i just draw it on paper,with my 90 degree ruler, and i got d is 6,6 so d^2=43,56 which mean 43 or 44 i answer 44 for the first time and it true :D
Problem Loading...
Note Loading...
Set Loading...
Let M , N be midpoints of A D , B C respectively.
So that, MN is a symmertry axis of rectangle A B C D , infer that MN is perpendicular to X 1 X 2 . ( 1 )
We have X 1 X 2 is a chord of circle that has center M . ( 2 )
From ( 1 ) and ( 2 ) , we have X 1 and X 2 are symmetric by M N so d 2 = 4 N X 1 2 . ( 3 )
Apply Pythagorean theorem to right triangle N X 1 M , we have N X 1 2 = M X 1 2 − M N 2 = ( 2 A D ) 2 − A B 2 = 6 2 − 5 2 = 1 1 . ( 4 )
(note: X 1 M is a median of right triangle X 1 A D )
From ( 3 ) and ( 4 ) , we have d 2 = 4 4 .